Hukum Islam dan Efek Jera Pemidanaan di Indonesia - Muhammad Taufan Djafri; Ni’man Samad; Mustaufiq Mustaufiq; Sabri Samin; Misbahuddin Misbahuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The main problem in this study is the description of Islamic law and the deterrent effect of punishment in Indonesia. Based on the subject matter, this study aims to find out the description of the deterrent effect of the perspective of Islamic law and its application in punishment in Indonesia, and to find out the effectiveness of Islamic law in creating a deterrent effect for criminals. This research is a library research with a descriptive and normative juridical approach. The results of the study show that the application of a deterrent effect in Islamic law is ḥudūd, kisas, kafarat, and takzir punishments. The application of a deterrent effect in sentencing in Indonesia is death penalty, imprisonment, confinement, fines, and punishment for the revocation of certain rights. The effectiveness of the deterrent effect of punishment according to Islamic law is to create benefit, uphold the rule of law and justice for humans and keep away from mafsada that will harm themselves and others